xxxxxxx - Salgueiro, Miriam Assunção Tazem; Leite, Nildes Raimunda Pitombo; Pereira, Reginaldo Luis; Viegaz, Osvaldo Estrela; Santana, Katia (Revista de Administração da UFSM, 2014)
In this article, two commercial films “Front of Class”, directed by Werner (2008) and “Door to Door”, directed by Shachter (2002) were studied from the perspective of the theme people management and its role in the insertion and maintenance of people with disabilities. They were part of an educational project developed with the qualitative approach, two perspectives of projects based on Moura e Barbosa (2011): research, conducted the investigation on the contribution of such a project on building skills of students in level undergraduates; learning, for developing a group of students under the orientation of teachers. Both perspectives of the project contributed to the maintenance of the inseparability of teaching, research and extension, the time eventually helped to minimize barriers erected, approaching teachers / students, teachers / teachers, students / students involved in the project. The observational study in film analysis, in the middle of its limitations and advantages, showed that the insertion and maintenance of persons with disabilities in organizations is not subject to be treated simplistically, since personal differences affect not only the environment but also organizational outcomes.